The Role of Digital Literacy in Mediating the Influence of Regulations and Organizational Support on Lecturer Career Development in East Nusa Tenggara - Paridy, Anggraeny; Man, Stanis; Fallo, Apryanus (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research is titled The Role of Digital Literature in Mediating the Influence of Regulation and Organization Support Towards the Growth of Lecturers’ Career in East Nusa Tenggara. Government regulations serve as a lecturer’s guide to the growth of their career. The role of Digital Literature is important to provide information and reports on the Lecturer’s growth. The purpose of this research is to figure out if Regulation, Organization Support has a significant impact on the growth of a Lecturer’s Career, and if the role of Digital Literature can mediate the influence of Regulation and Organization’s Support on the growth of one’s career. This research is being held in East Nusa Tenggara, the object of this research are lecturers who work in National University and Private University, the researched population are the entire lecturers that worked in East Nusa Tenggara, the samples were set as much as 174 lecturers according to the questioner given In determining the sampling technique with random action sampling, the analytical tool used is SEM PLS. The result of this research is the Regulation and Organization Support, which is significant for the Growth of lecturers’ careers and for understanding how Digital Literature mediates the influence of Regulation and Organization Support on lecturers’ careers in East Nusa Tenggara. This is supported by achieving the optimal value or significance, by the contribution of each variable studied, or by a robust coefficient of determination.